A casa burguesa do Porto no séc. XXI. Diálogo entre o habitar contemporâneo e a identidade dos espaços interiores burgueses. - Andreia Patricia Alba da Costa (2013)
Within a contemporary world, Porto is notable for its own identity, a medieval picture in an historic center that once served as primary housing area. Constantly losing their inhabitants for neighboring municipalities, the city became aged, serving as an employment center and a pole of education for those who have moved out of its limits. Like people, the architecture was also aging and gradually was leaving to meet the needs of society, resulting in a Porto destroyed and empty. Rehabilitate the center is essential and for make this happen, it is necessary to take measures of intervention and rehabilitation of their buildings, making them habitable again and adapted to contemporary needs in order to seduce a population that has long left them for new spaces. The typical house of Porto served a society now defunct, the Bourgeoisie, in a time of social, economic and political changes. But because rehabilitation is not only the restructuring of a space, it is essential to understand the relationship between the architecture of the house with the context in which it was built, realizing how the habitation responded to the wishes of the bourgeois. This dissertation intends to establish a counterpoint between past society and current society, between the century XIX and XXI, in an attempt to figure out what to keep, what to eliminate and what to add, building contemporary structures in continuity with the past, and keeping the characteristic identity of the interiors.